Methodological foundations of teaching the discipline "Chemical Technology" - R.O. Sarsenova; D.A. Kassymbekova; S. A. Tungatarova; Zh K. Korganbayeva (Theoretical Hypotheses and Empirical Results, 2023)
The relevance of this study is due to the solution of the problem of forming a high level of knowledge and practical skills developed in the course of studying the discipline "Chemical Technology", contributing to improving the quality of training of qualified specialists, including for the development and improvement of life support processes. The purpose of the article is to develop methodological foundations for the organization of educational activities in the study of chemical technology. The leading method of studying this problem is testing, according to the development of T.D. Dubovitskaya’s "Orientation of academic motivation” allows students to identify the degree of development of internal motivation for the educational process. The article presents the methodological foundations of the organization of educational activities for the study of the subject of chemical technology, which allows students to form an interest, internal motivation, a high level of understanding, and assimilation of this discipline. It is based on a health-saving environment during the acquisition of knowledge, the form of teaching the subject, the formation of an understanding of the value and impact of knowledge on life, the creation of models for the application of knowledge in practice, the basics of the environmentally oriented use of chemical technologies in the development of scientific and technological progress of life support based on criteria such as motivational-value, cognitive-informational, ecological-creative and cultural-aesthetic. The methodological foundations of the organization of the educational process on the subject of "Chemical Technology" contribute to the formation of a holistic understanding of the use of knowledge in practice and in scientific activity for the development and preservation of the well-being of society and ecology, in which specialists in this field and in general in chemistry play one of the fundamental roles. This has practical significance for the entire education system and the well-being of society.